2022
DOI: 10.1371/journal.pone.0268770
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of acute chorioretinal changes due to intensive physical exercise in young adults

Abstract: Purpose There is abundant evidence on the benefits of physical activity on cardiovascular health. However, there are only few data on the acute effects of physical exercise on the retina and choroid. Our aim was the in vivo examination of chorioretinal alterations following short intense physical activity by spectral domain optical coherence tomography (SD-OCT). Methods Twenty-one eyes of 21 healthy, young subjects (mean age 22.5 ± 4.1 years, 15 males and 6 females) were recruited. Macular scanning with a SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Although this trend was also present in the single nuclear layers of the retina, mostly in the outer retina, these changes did not reach statistical significance at the level of segmentation results. Nonetheless, these changes resemble the observations made in young adults undergoing vita maxima strain wherein the same acute significant thinning was described, followed by significant thickening of the total retina and the nuclear layers (Szalai et al, 2022). In the young adult population, it has been postulated that the reason behind the observations might be twofold.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although this trend was also present in the single nuclear layers of the retina, mostly in the outer retina, these changes did not reach statistical significance at the level of segmentation results. Nonetheless, these changes resemble the observations made in young adults undergoing vita maxima strain wherein the same acute significant thinning was described, followed by significant thickening of the total retina and the nuclear layers (Szalai et al, 2022). In the young adult population, it has been postulated that the reason behind the observations might be twofold.…”
Section: Discussionsupporting
confidence: 81%
“…Second, in case the acute changes in IOP might play a role in the acute thinning observed at 1 min (either per se or by complementing the vasogenic response), it might be postulated that acute exercise leads to less IOP increase in the senior cohort. However, the elevation of BP during exercise in the elite senior athletes was very similar to that in young athletes due to the controlled conditions in the senior cohort to avoid CV complications (Szalai et al, 2022).…”
Section: Discussionmentioning
confidence: 71%
“…Given that physical activity is known to alter blood flow in a variety of organs and tissues, choroidal effects would seem plausible. However, while early studies showed changes in choroidal blood flow with exercise as measured with laser Doppler flowmetry, 160 most studies examining ocular parameters shortly after physical exercise did not detect significant changes in choroidal thickness, 151 , 161 164 with the exception in some studies of a temporary choroidal thickening a few minutes after exercise, followed by a reduction in thickness. 4 , 150 On the other hand, thinning of the choroid was observed after endurance exercise (marathon running).…”
Section: Short-term Influences On Choroidal Thicknessmentioning
confidence: 99%
“…Additionally, the OCT follow-up feature was utilized to ensure that the OCT line image remained in the same position during baseline and follow-up visits. To order to reduce the influence from major known confounders to ChT and AL including physical activity [25] , near work [26] , and ambient light [27] . Subjects were instructed to spend 15min in a room with low photopic ambient light before the measurements, while focusing on a target placed at 3 m. The OCT scans were obtained with participants wearing MFGPCLs, given previous research indicating minimal impact of contact lens (CL) wear on OCT imaging of macular thickness [28] and retinal nerve fiber layer thickness [29] .…”
Section: Measurementsmentioning
confidence: 99%